2018
DOI: 10.1002/lary.27236
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes and prognosis in submandibular gland malignant tumors: A multicenter study

Abstract: 4. Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 37 publications
2
4
0
1
Order By: Relevance
“…Nodal status (pN+ vs pN0) is considered among the most important prognostic factors in MSG carcinoma [6,7,[27][28][29][30][31][32][33]. Our overall rate of nodal involvement was 31.4%, in keeping with previously reported figures, which range between 11.8% and 37% [1,4,9,14,30,34].…”
Section: Nodal Prognostic Factorssupporting
confidence: 90%
“…Nodal status (pN+ vs pN0) is considered among the most important prognostic factors in MSG carcinoma [6,7,[27][28][29][30][31][32][33]. Our overall rate of nodal involvement was 31.4%, in keeping with previously reported figures, which range between 11.8% and 37% [1,4,9,14,30,34].…”
Section: Nodal Prognostic Factorssupporting
confidence: 90%
“…In our study, occult metastases in level I were nearly almost found in patients with submandibular gland carcinoma, and nearly half of the patients with pN+ submandibular gland carcinomas had metastases in nock node level I (8/17, 47%). This supports the recommendation to include lymph nodes from levels I, II, and III in the primary surgical treatment of submandibular gland carcinomas, as suggested by other studies 38,60 …”
Section: Discussionsupporting
confidence: 87%
“…Regional metastases have been reported in 27%–40% of patients with submandibular carcinomas, 60‐62 and occult metastases have been reported in up to 22% of patients with submandibular carcinomas who were treated with END 2 . Considering that submandibular gland carcinomas frequently are high‐grade histological subtypes, 60 END should be relevant for most of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In verschiedenen Studien wurden positive Resektatränder bei etwa 40 % der Patient*innen festgestellt. Diese waren mit einem kürzeren rezidivfreien Überleben [13] und verkürztem Gesamtüberleben verbunden [5,18] Bei klinisch oder sonographisch auffälligen zervikalen Lymphknoten ist die ipsilaterale Neck-Dissection obligatorisch. Das Management des als cN0-Stadium beurteilten Halses wird kontrovers diskutiert [1,23].…”
Section: Tumorarten Und Therapieansätzeunclassified